2016
DOI: 10.1177/0954406216631002
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reconstruction and performance assessment of an eroded centrifugal pump impeller

Abstract: Emphasis is placed on the performance of a two-stage pump equipped with an eroded impeller. Non-contact reverse engineering technique is utilized to acquire the point data constituting the three-dimensional geometrical model of the eroded impeller. With computational fluid dynamics, both the operation performance of the pump and flow patterns adjacent to the eroded blade surface are obtained. For comparison, the corresponding undamaged impeller is investigated as well. Preferable fidelity of the approach of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The computational fluid dynamics (CFD) technique helps to deepen the understanding of cavitating flows in the pump (Kang et al 2017a). Based on numerical results, unsteady flows in a hydraulic turbine were described in Wu et al (2012), which demonstrated the ability of CFD in predicting flow phenomena associated with the rotating impeller.…”
Section: Introductionmentioning
confidence: 99%
“…The computational fluid dynamics (CFD) technique helps to deepen the understanding of cavitating flows in the pump (Kang et al 2017a). Based on numerical results, unsteady flows in a hydraulic turbine were described in Wu et al (2012), which demonstrated the ability of CFD in predicting flow phenomena associated with the rotating impeller.…”
Section: Introductionmentioning
confidence: 99%